# How do you write an equation of a line with points (-2,-4), (2,4)?

Feb 12, 2017

$\left(y + \textcolor{red}{4}\right) = \textcolor{b l u e}{2} \left(x + \textcolor{red}{2}\right)$

Or

$\left(y - \textcolor{red}{4}\right) = \textcolor{b l u e}{2} \left(x - \textcolor{red}{2}\right)$

Or

$y = 2 x$

#### Explanation:

he point-slope formula can be used to find the equation. First we must determine the slope. The slope can be found by using the formula: $m = \frac{\textcolor{red}{{y}_{2}} - \textcolor{b l u e}{{y}_{1}}}{\textcolor{red}{{x}_{2}} - \textcolor{b l u e}{{x}_{1}}}$

Where $m$ is the slope and ($\textcolor{b l u e}{{x}_{1} , {y}_{1}}$) and ($\textcolor{red}{{x}_{2} , {y}_{2}}$) are the two points on the line.

Substituting the values from the points in the problem gives:

$m = \frac{\textcolor{red}{4} - \textcolor{b l u e}{- 4}}{\textcolor{red}{2} - \textcolor{b l u e}{- 2}}$

$m = \frac{\textcolor{red}{4} + \textcolor{b l u e}{4}}{\textcolor{red}{2} + \textcolor{b l u e}{2}} = \frac{8}{4} = 2$

The point-slope formula states: $\left(y - \textcolor{red}{{y}_{1}}\right) = \textcolor{b l u e}{m} \left(x - \textcolor{red}{{x}_{1}}\right)$

Where $\textcolor{b l u e}{m}$ is the slope and $\textcolor{red}{\left(\left({x}_{1} , {y}_{1}\right)\right)}$ is a point the line passes through.

Substituting the slope we calculated and the first point gives:

$\left(y - \textcolor{red}{- 4}\right) = \textcolor{b l u e}{2} \left(x - \textcolor{red}{- 2}\right)$

$\left(y + \textcolor{red}{4}\right) = \textcolor{b l u e}{2} \left(x + \textcolor{red}{2}\right)$

We can also substitute the slope we calculated and the second point giving:

$\left(y - \textcolor{red}{4}\right) = \textcolor{b l u e}{2} \left(x - \textcolor{red}{2}\right)$

We can also solve this equation for $y$ to put the equation in the familiar slope-intercept form. The slope-intercept form of a linear equation is: $y = \textcolor{red}{m} x + \textcolor{b l u e}{b}$

Where $\textcolor{red}{m}$ is the slope and $\textcolor{b l u e}{b}$ is the y-intercept value.

$y - \textcolor{red}{4} = \left(\textcolor{b l u e}{2} \times x\right) - \left(\textcolor{b l u e}{2} \times \textcolor{red}{2}\right)$

$y - \textcolor{red}{4} = 2 x - 4$

$y - \textcolor{red}{4} + 4 = 2 x - 4 + 4$

$y - 0 = 2 x - 0$

$y = 2 x$